ANALISA PENGARUH LAJU KALOR TERHADAP EFISIENSI TERMAL PLTU SINTANG (3X7 MW) - ., NAPIANUS BUDIANTO (Jurnal Teknik Elektro Universitas Tanjungpura, 2018)
In order to meet the electricity demand in the area Sintang, which is still a shortage of power supply, PLN plans to build new plants. New plant that will be developed include small-scale coal based power plant. One is the power plant which has a capacity Sintang power 21 MW, located in RT 06 / RW 03 Ringin Sungai Dusun Exodus Kapuas Kanan Hilir, District Sintang, Sintang, West Kalimantan Province. Sintang power plant (3X7 MW) using coal fuel with a calorific value of 3800 kcal / kg. The performance of a steam power plant depends on all the supporting components. One of them is the age factor of the use of these components, the longer the component is used then the efficiency will decrease, so that the heat energy needed to generate electricity increases. The purpose of this paper is to analyze the performance of the power plant Sintang (3 x 7 MW) of load effects on specific coal fuel consumption (SFC), the rate of heat, and thermal efficiency. Calculation shows specific fuel consumption of coal lowest gross and net 1.41 kg / kWh and 1.61 kg / kWh in the highest load of 6978 kW and 1.84 kg / kWh and 2.21 kg / kWh in 3764 kW load while the pace lowest gross and net calorific 5368.96 kcal / kWh and 6150.78 kcal / kWh in 6978 and the highest load 7001.96 kcal / kWh and 8422.45 kcal / kWh in 3764 kW load as well as gross and net thermal efficiency of 12.28 lows % and 10.21% at the highest load of 3764 kW and 16.01% and 13.98% in 6978 kW load. The purpose of this paper is to analyze the performance of the power plant Sintang (3 x 7 MW) of load effects on specific coal fuel consumption (SFC), the rate of heat, and thermal efficiency. Calculation shows specific fuel consumption of coal lowest gross and net 1.41 kg / kWh and 1.61 kg / kWh in the highest load of 6978 kW and 1.84 kg / kWh and 2.21 kg / kWh in 3764 kW load while the pace lowest gross and net calorific 5368.96 kcal / kWh and 6150.78 kcal / kWh in 6978 and the highest load 7001.96 kcal / kWh and 8422.45 kcal / kWh in 3764 kW load as well as gross and net thermal efficiency of 12.28 lows % and 10.21% at the highest load of 3764 kW and 16.01% and 13.98% in 6978 kW load. The purpose of this paper is to analyze the performance of the power plant Sintang (3 x 7 MW) of load effects on specific coal fuel consumption (SFC), the rate of heat, and thermal efficiency. Calculation shows specific fuel consumption of coal lowest gross and net 1.41 kg / kWh and 1.61 kg / kWh in the highest load of 6978 kW and 1.84 kg / kWh and 2.21 kg / kWh in 3764 kW load while the pace lowest gross and net calorific 5368.96 kcal / kWh and 6150.78 kcal / kWh in 6978 and the highest load 7001.96 kcal / kWh and 8422.45 kcal / kWh in 3764 kW load as well as gross and net thermal efficiency of 12.28 lows % and 10.21% at the highest load of 3764 kW and 16.01% and 13.98% in 6978 kW load.Keywords : Steam Power Plant, Specific Fuel Consumption, Power Plant Analysis